ANÁLISIS DOCTRINARIO Y JURÍDICO DE LA CRIMINALIDAD COMPLEJA EXISTENTES EN LOSCENTROS DE PRIVACIÓN DE LIBERTAD DEL ECUADOR - Pinzón Conza., Santos Bolívar (2024)
The following work is entitled “Doctrinal and Legal Analysis of the Complex Criminality existing in Ecuador's Prisons”. It is evident that prisons face the challenge of housing inmates involved in a variety of crimes, including drug trafficking, extortion, and other organized crimes, which is why he is interested in conducting research and conducting an analysis. Consequently, tensions between inmates are created within prison facilities, which can cause fights, riots, and situations of violence among inmates, and criminal gangs operate within prisons, posing a threat to both inside and outside security. Overcrowding and a lack of adequate resources are also factors contributing to the problem, as they make it difficult to separate dangerous inmates and access rehabilitation programs. Corruption among prison guards and public officials working in these centers also contributes to the problem. Furthermore, the present study indicates violations of some of the rights and guarantees of persons deprived of liberty, which have been recognized in Ecuador's Constitution, but have not been effectively implemented by the government. Thus, the purpose of this research is to ensure a better quality of life for persons deprived of liberty, as well as employment and educational opportunities. A variety of materials and methods were incorporated into the respective Curricular Integration Work in order to allow the development of the same, which included the development of surveys and interviews with members of the legal profession. Based on those results, it was proposed to develop pro-positive guidelines as a means to guarantee the fulfillment of those individuals deprived of liberty, those rights that are currently being violated as a result of a complex criminality in Ecuador's centers for deprivation of liberty.